Time series analysis of the determinants of non-oil manufacturing exports within business environment in Nigeria (Multi-disciplinary Journal of Research and Development Perspectives, 2026)
Manufacturing export in Nigeria today has become the most dynamic sector with the highest level of production globally and based on the significant performance, the study aimed at ascertaining whether specific business environmental factors are major drivers of manufacturing export performance in Nigeria. The model was anchored on Export-led growth theory. Panel data analytical framework using survey sampling technique and a cross sectional time series technique was employed to investigate 20 manufacturing firms listed in the Nigerian stock exchange of 2018 between 2007 to 2018. The panel result shows that the estimated equation is statistically significant and has a good fit. It was also revealed that economic and regulatory quality, government efficiency, trade relations, agriculture, conglomerate and service industries are major drivers of manufacturing export performance. The study concludes that Government should make strong and proactive economic and regulatory policies to provide monitoring and evaluation programs to check the activities of non-oil exporting firms to make sure those available financial resources are used to generate aggregate net worth, increase sales, and enhance profitability. Further and extensive research should be carried out disaggregating ownership into public, private and foreign sectors to determine the one with higher export propensity, effective performance and aggregate output.
Keywords: Manufacturing; Performance; Output; Export; Firms